Understanding and measuring morphological complexity - Baerman, Matthew; Brown, Dunstan; Corbett, Greville G. (Oxford Oxford University Press, 2015)
This work aims to assess the nature of morphological complexity, and the properties that distinguish it from the complexity manifested in other components of language. Chapters highlight novel perspectives on conceptualizing morphological complexity, and offer concrete means for measuring, quantifying and analysing it
What is Morphological Complexity? -- Understanding and measuring morphological complexity: An introduction / Matthew Baerman, Dunstan Brown, Greville G. Corbett -- Dimensions of morphological complexity / Stephen R. Anderson -- Understanding Complexity -- Rhizomorphomes, meromorphomes, and metamorphomes / Erich R. Round -- Morphological opacity: Rules of referral in Kanum verbs / Mark Donohue -- Morphological complexity à la Oneida / Jean-Pierre Koenig, Karin Michelson -- Gender-number marking in Archi: Small is complex / Marina Chumakina, Greville G. Corbett -- Measuring Complexity -- Contrasting modes of representation for inflectional systems: Some implications for computing morphological complexity / Gregory Stump, Raphael A. Finkel -- Computational complexity of abstractive morphology / Vito Pirrelli, Marcello Ferro, Claudia Marzi -- Patterns of syncretism and paradigm complexity: The case of Old and Middle Indic declension / Paolo Milizia -- Learning and the complexity of Ø-marking / Sebastian Bank, Jochen Trommer
Includes bibliographical references (pages 205-215) and indexes.
Keywords: Grammar, Comparative and general -- Inflection; Complexity (Linguistics.